Sexual functioning in people with stable chronic diseases - Pais-Ribeiro, José Luís (2015)
Backgound - In developed countries people are living longer and the incidence of chronic disease is increasing. Chronic disease and its treatments can have a negative impact on sexual functioning and sexual satisfaction. Aim of study - To explore and to compare sexual function and sexual satisfaction in people with stable chronic diseases.